Psychosocial consequences of a reduced ability to eat for patients with cancer and their informal caregivers: A qualitative study. (December 2020) - Lize, Nora; Raijmakers, Natasja; van Lieshout, Rianne; Youssef-El Soud, Maggy; van Limpt, Anouk; van der Linden, Mecheline; Beijer, Sandra
Abstract: Purpose: Patients with cancer often experience a reduced ability to eat. This can have psychosocial consequences for both patients and informal caregivers. Current literature is mainly focused on patients with end stage advanced disease and cancer cachexia. This qualitative study provides new insights in the field of Psycho-Oncology by exploring psychosocial consequences of a reduced ability to eat in patients in different stages of the disease and in recovery and remission. Method: Semi-structured interviews (n = 26) were conducted in patients with head and neck, lung cancer or lymphoma. Patients' informal caregivers participated in 12 interviews. All interviews were recorded, transcribed and thematically analysed using Atlas.ti. Results: Four themes emerged related to psychosocial consequences of a reduced ability to eat: struggle with eating, high sense of responsibility, misunderstanding by social environment and social consequences. Emotions mentioned by patients and informal caregivers were: anger, anxiety, disappointment, grief and sadness, guilt, powerlessness and shame. The theme social consequences was related to: less pleasure experienced and the social strategies: adjust, search for alternatives and avoid. Conclusion: Patients with cancer and their informal caregivers experience a wide range of psychosocial consequences of reduced ability to eat during all phases of the disease trajectory and in recovery and remission. It is important to recognise and acknowledge this struggle to optimise future care. Highlights: Reduced ability to eat due to cancer can result in psychosocial issues. These psychosocial issues occur in all stages of the disease trajectory. Patients with cancer feel misunderstood in their struggle with eating. Informal cancer caregivers feel responsible for patients' reduced ability to eat. Healthcare professionals must acknowledge these psychosocial eating issues.